Thresholds of hypoxia of two Red Sea coral species (Porites sp. and Galaxea fascicularis) - Jacqueline V. Alva García; Shannon G. Klein; Taiba Alamoudi; Silvia Arossa; Anieka J. Parry; Alexandra Steckbauer; Carlos M. Duarte (Frontiers in Marine Science, 2022)
Anthropogenic pressures have driven large-scale declines in coral cover on >50% of tropical coral reefs. Most research efforts have focused on ocean warming, ocean acidification, and overfishing impacts. Despite increasing instances of reef-associated hypoxic events, the role of reduced O 2 in affecting coral reef performance is largely unknown. Here, we assessed the hypoxic thresholds of two Red Sea coral species: Porites sp. and Galaxea fascicularis . We exposed coral fragments of both species to one control treatment (6.8 mg O 2 L −1 ) and three reduced dissolved oxygen treatments (5.25, 3.5, and 1.25 mg O 2 L −1 ) during a 10-day experiment. Across the two species, maximum ( Fv / Fm ) and effective ( F′ / F m ′ ) photochemical efficiency, chlorophyll a , and dark respiration declined under the lowest O 2 treatment (1.25 mg O 2 L −1 ). Porites sp. coral fragments, however, were remarkably resistant and showed no signs of sublethal bleaching after 10 days of exposure to reduced O 2 . Conversely, 17% of G. fascicularis fragments bleached after only three nights of exposure to the lowest O 2 treatment (1.25 mg O 2 L −1 ). Our data show that longer-term hypoxic events (i.e., days to weeks) can induce coral bleaching, but these effects depend on the extent of O 2 reduction and are likely species-specific. Importantly, the levels of O 2 usually defined as hypoxic (~2.0 to 2.8 mg O 2 L −1 ) do not adequately capture the thresholds reported here. Hence, further research is urgently needed to more accurately describe the vulnerability of coral taxa to hypoxic and anoxic events.